2002
DOI: 10.22358/jafs/67895/2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Fusarium</i> toxin contaminated wheat grain and of a detoxifying agent on rumen physiological parameters and <i>in sacco</i> dry matter degradation of wheat straw and lucerne hay in wethers

Abstract: Wethers equipped with a rumen fistulae were subjected to four dietary treatments in consecutive experiments. The treatments consisted of rations containing wheat grain and pasture hay at a ratio of 1 to 1 on a dry matter basis. Two wheat grain batches were fed either in the absence or presence of a detoxifying agent (Mycofix^Plus, Biomin GmbH, Herzogenburg, Austria). One wheat grain batch served as the uncontaminated control wheat whereas the other batch contained the Fusarium toxins deoxynivalenol (DON) and z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Therefore, DON concentrations lower than 5 mg per kg seem to not affect rumen fermentation, with the exception of fibre fractions. This fact was reflected by the unchanged amounts of SCFA both in the present in vitro and earlier in vivo studies (Da¨nicke 2002;Da¨nicke et al 2005). In contrast, higher fermentation rates (Seeling et al 2006) and differences in feed intake (Keese et al 2008b) changed the pattern of SCFA when toxin-contaminated grain was fed.…”
Section: Ruminal Fermentation and Microbial Protein Synthesissupporting
confidence: 52%
“…Therefore, DON concentrations lower than 5 mg per kg seem to not affect rumen fermentation, with the exception of fibre fractions. This fact was reflected by the unchanged amounts of SCFA both in the present in vitro and earlier in vivo studies (Da¨nicke 2002;Da¨nicke et al 2005). In contrast, higher fermentation rates (Seeling et al 2006) and differences in feed intake (Keese et al 2008b) changed the pattern of SCFA when toxin-contaminated grain was fed.…”
Section: Ruminal Fermentation and Microbial Protein Synthesissupporting
confidence: 52%
“…They found a decrease in SCFA production and a reduction in gas production. Dänicke (2002) reported that rumen pH and concentrations of ammonia and SCFA in wethers fed a ration of hay and Fusarium toxin‐contaminated wheat (4.6 mg of DON and 0.34 mg ZON per kg of ration DM) were not influenced by contamination of the wheat. Accordingly, the Fusarium contamination did not modify ruminal pH of dairy cows in the current study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Fusarium infection of wheat can lead to alterations of nutrient composition and cell wall compounds of the infected grain because of higher protease, amylase and several non‐starch polysaccharide (NSP)‐degrading enzyme activities (Kang and Buchenauer, 2000; Matthäus et al., 2004). However, knowledge regarding the effects of Fusarium ‐contaminated feed and/or DON and ZON on ruminal nutrient utilization (Dänicke, 2002; Dänicke et al., 2005) and milk composition (Noller et al., 1979; Cote et al., 1986; Whitlow et al., 1986; Charmley et al., 1993; Ingalls, 1996) is still lacking. Moreover, no information is available about effects of a passage‐rate‐dependent ruminal fermentation of Fusarium ‐contaminated feed.…”
Section: Introductionmentioning
confidence: 99%
“…Immediately before the morning feeding, a lower concentration of acetate with inclusion of FUS was also observed in the present study with cows (data not shown, p = 0.06). Studies with sheep, however, showed no significant effects of Fusarium toxin‐contaminated wheat on the acetate‐to‐propionate ratio (Dänicke, 2002). Variable results in SCFA production could be attributed to interactions of Fusarium toxins with other factors such as the composition of diet, the dosage and duration of toxin exposure and the animal species (Seeling and Dänicke, 2005).…”
Section: Discussionmentioning
confidence: 99%